2020
DOI: 10.1002/mgg3.1250
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological features: The next precise step for SCN2A developmental epileptic encephalopathy

Abstract: BackgroundTo investigate the relationships among phenotypes, genotypes, and funotypes of SCN2A‐related developmental epileptic encephalopathy (DEE).MethodsWe enrolled five DEE patients with five de novo variants of the SCN2A. Functional analysis and pharmacological features of Nav1.2 channel protein expressed in HEK293T cells were characterized by whole‐cell patch‐clamp recording.ResultsThe phenotypes of c.4712T>C(p. I1571T), c.2995G>A(p.E999K), and c.4015A>G(p. N1339D) variants showed similar charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…Several recently reported variants in SCN2A from patients with childhood epilepsy also presented with evidence indicating developmental impairments (Miao et al, 2020). The terminology of "developmental and/or epileptic encephalopathy" thus has been used to imply that the developmental impairments could occur independently of seizures (Maljevic et al, 2017;Scheffer et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Several recently reported variants in SCN2A from patients with childhood epilepsy also presented with evidence indicating developmental impairments (Miao et al, 2020). The terminology of "developmental and/or epileptic encephalopathy" thus has been used to imply that the developmental impairments could occur independently of seizures (Maljevic et al, 2017;Scheffer et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Several recently reported variants in SCN2A from patients with childhood epilepsy also presented with evidence indicating developmental impairments. 68 The terminology of "developmental and/or epileptic encephalopathy" thus has been used to imply that the developmental impairments could occur independently of seizures. 69,70 Indeed, profiling of patients with the L1342P variant revealed developmental disorders.…”
Section: Discussionmentioning
confidence: 99%
“…At present, voltage-gated sodium channel genes such as SCN1A , SCN2A , SCN3A , and SCN8A were reported to be causative genes of epilepsy ( Ademuwagun et al, 2021 ), among them SCN2A has been reported to be the second most common, next only to SCN1A , the first reported causative gene for epilepsy ( Heyne et al, 2019 ). Epilepsy caused by SCN2A variants mostly starts in early childhood and has a wide phenotypic spectrum, ranging from self-limited epilepsy with a favorable outcome to developmental and epileptic encephalopathy, and most of them respond well to sodium channel blockers (SCBs) ( Grinton et al, 2015 ; Trump et al, 2016 ; Dilena et al, 2017 ; Flor-Hirsch et al, 2018 ; Kim et al, 2020 ; Melikishvili et al, 2020 ; Miao et al, 2020 ; Penkl et al, 2021 ). China has a large population and a large number of epilepsy children.…”
Section: Introductionmentioning
confidence: 99%